FINANCIAL PERFORMANCE ANALYSIS OF COAL COMPANIES LISTED ON IDX, 2014-2016 PERIOD - Arsa Arsa (Jurnal Inovasi Penelitian, 2022)
Coal is one of the most popular stock commodities from the past until now. Coal stock investment is one of the most desirable types of investment because it provides the highest yield. Although the purchase price is rather high, it does not reduce demand. As a leading mining commodity, coal mining has mushroomed in Sumatra, Kalimantan, Sulawesi, and others. Coal from mining in Indonesia is marketed to the domestic and export markets. Research objectives. To analyze and assess the financial performance of Coal Companies listed on the IDX for the period 2018-2021 based on the ratio of liquidity, solvency, activity and profitability. The research method used is descriptive research, the research population is 10 coal companies listed on the Indonesia Stock Exchange. Sampling was carried out using a purposive sampling technique, namely, a deliberate technique The purpose of this study is to analyze and assess the financial performance of coal companies listed on the IDX for the period 2022 – 2022, based on liquidity, solvency and profitability ratios. Research results 1. It can be said that the financial performance of coal companies is good in terms of the high current ratio value, the company is able to pay or pay off all of its current obligations in the near future. 2. It can be said that the financial performance of coal is good in terms of the capital ratio value which means that the company is able to pay its obligations 3. It can be said that the financial performance of coal companies is good in terms of the DAR and DER values, the higher the value generated means the total assets of coal companies owned in financed by debt and the interest expense borne by the company is also high 4. It can be said that the financial performance of coal companies is not good as seen from the ROI analysis which means that the profit earned on its operational activities is low. Furthermore, the financial performance of coal companies is good as seen from the ROE analysis which means that coal companies are very productive in carrying out their activities and the role of managers in successfully managing businesses or businesses.